The Islamic Call: Al-Farabi's Philosophical Perspectives on Navigating the Dilemma of Modernity in Establishing an Ideal State - Masmuni Mahatma (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
This study aims to explore and analyze the concepts proposed by Al-Farabi regarding the ideal state or the virtuous city in order to enrich our understanding of how Islamic states can address the challenges of modernity and democracy while maintaining a balanced approach to core Islamic values. The research adopts a literature review methodology, collecting and analyzing various primary and secondary sources related to Al-Farabi’s political thought on the concept of the ideal state. Al-Farabi;s ideas about the ideal state or virtuous city provide crucial principles for constructing a state that prioritizes the happiness of its society. In the modern context, Al-Farabi’s thoughts can serve as inspiration and guidance for societies in developing inclusive, just, and sustainable political systems. The holistic concept of political wisdom reminds us of the significance of integrating moral, spiritual, and rational values in the decision-making process. By considering these aspects, a state can create conditions that support the happiness and perfection of individuals.